Forming Mechanism of Political Risks in International Construction Projects: From the Perspective of Chinese Contractors - Ullah, Safi; Deng, Xiaopeng; Chang, Tengyuan (Frontiers in Built Environment, 2019)
The performance is analysed from the perspective of the characteristics of overseas business of Chinese contractors and political risks. Based on the results of this research project, it further analyse the funds and pricing model of Chinese Contractors Overseas Projects, as well as their ability to withstand political risks and coping strategies. This study aims to explore the statistical analysis of the project system and transnational operations to political risks in international construction projects. This research is based on one belt and one road. The questionnaire was distributed to 100 Chinese international contractors in the form of emails. Of the 100 contractors, 50 are in the top 225 of the 2017 ENR. Researches based on the project, each project only fill in a questionnaire, the final recovery of 370 copies, and recovery rate of 37%. 370 respondents are from 46 Chinese international contractors, of which 28 (60.87%) are from top ENR225 enterprises and 18 (39.13%) are from other enterprises. This survey reflects the general situation of political risks of Chinese contractors in overseas project management. Generally speaking, Chinese contractors are facing higher political risks, and they do not attach enough importance to political risks, and their ability to deal with political risks. This research study is a useful reference for managing the political risks for international contractors when expanding into this emerging market.